The Influence of Work Discipline, Organizational Commitment, and Work Environment on Employee Performance at RSUD Brebes Regency - Edy Santoso (International Journal of Management, Economic, Business and Accounting, 2026)
Purpose of the study — Brebes Regional Hospital as a referral hospital in Brebes district has various facilities that support examinations and services to the community. In general, the Brebes Regional Hospital has performed well, but there are still several complaints submitted to the Brebes Regional Hospital. The performance of RSUD Brebes is quite good, but from the results of the assessment of organizational performance there are still things that have not been achieved in the hospital quality indicators of RSUD Brebes in 2023. This research aims to analyze the influence of work discipline, organizational commitment and work environment on employee performance at Brebes Regional General Hospital. Research method— This research was conducted using multiple linear analysis, with the t test and f test as hypothesis testing. The sampling technique uses a non-probability sampling technique with a purposive sampling method. The test equipment used for data processing used SPSS version 25 software. The data collection technique was carried out by distributing questionnaires. The analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test and coefficient of determination. Result— summarize the result or findings of your study The results of the coefficient of determination show that employee performance which is influenced by work discipline, organizational commitment and work environment variables is 71.3% while the remaining 28.7% is influenced by other factors not included in this research. Based on the results of the hypothesis testing carried out, it can be concluded that the significance value is <0.05 and tcount > ttable, so the independent variable partially influences the dependent variable. Conclusion—The results of testing this hypothesis show that work discipline, organizational commitment and the work environment simultaneously have a positive and significant effect on employee performance.